Effect of Linseed Oil Feeding on Serum Lipids and Fatty Acid Profile of Breast and Thigh Muscle in Broiler Chicken - Shunthwal, Jyoti; A.S. Yadav, A.S. Yadav; Sihag, Sajjan; Kumar, Rakesh; Baloda, Saurabh; ., Promila; Sheoran, Nancy (Indian Journal of Animal Nutrition, 2018)
Three hundred, day-old, commercial broiler chicks were randomly distributed into 5 treatment groups with 6 replicates of 10 chicks in each replicate for a period of 6 weeks. The birds in control group (T1) were offered maize and soybean meal based diet having sunflower oil @ 4% and 5% in starter and finisher diet,respectively. While in treatments T2, T3, T4 and T5 sunflower oil of basal diet was replaced with linseed oil @ 25, 50, 75 and 100%, respectively. The contents of palmitic acid and stearic acids in thigh muscle decreased (P